Dielectric, Ferroelectric and Piezoelectric Properties of the Lead Free 0.9BaTiO3-(0.1-x)Bi0.5Na0.5TiO3-xBi(Mg0.5Ti0.5)O3 Solid Solution. Issue 1 (2nd January 2016) - Mayamae, Jitkasem; Sukkha, Usa; Niemchareon, Surasak; Muanghlua, Rangson; Vittayakorn, Naratip
Abstract : Solid solution of 0.9BaTiO3 -(0.1- x )Bi0.5 Na0.5 TiO3 - x Bi(Mg0.5 Ti0.5 )O3 (BT-BNT- x BMT) system, where x = 0.00, 0.02, 0.04, 0.06, 0.08, 0.10, was synthesized by the solid state reaction. Dense BT-BNT- x BMT ceramics were obtained by sintering at 1, 150–1, 250˚C for 4 h. The effect of BMT on crystal structure and electrical property of BT-BNT ceramics was investigated as a function of composition, x, using X-ray diffraction, dielectric spectroscopy, hysteresis and strain measurements. The crystal structure of solid solution BT-BNT- x BMT, where x = 0.00-0.10, successively transforms from tetragonal to pseudocubic symmetry, with increased BMT concentration. Temperature dependence of dielectric constant ( ϵr ) and dielectric loss ( tanδ ) for BT-BNT- x BMT at various frequencies showed that phase transition of ceramics changed from ferroelectric to relaxor-like behavior as BMT content increased. Furthermore, remanent polarization ( Pr ), coercive field ( Ec ) and the normalized strain ( d33 * ) of BT-BNT- x BMT ceramics tend to decrease with increasing BMT concentration.